2015
DOI: 10.2147/dddt.s86345
|View full text |Cite
|
Sign up to set email alerts
|

Gallic acid attenuates dextran sulfate sodium-induced experimental colitis in BALB/c mice

Abstract: Gallic acid (GA) is a polyhydroxy phenolic compound that has been detected in various natural products, such as green tea, strawberries, grapes, bananas, and many other fruits. In inflammatory bowel disease, inflammation is promoted by oxidative stress. GA is a strong antioxidant; thus, we evaluated the cytoprotective and anti-inflammatory role of GA in a dextran sulfate sodium (DSS)-induced mouse colitis model. Experimental acute colitis was induced in male BALB/c mice by administering 2.5% DSS in the drinkin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
71
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(78 citation statements)
references
References 57 publications
5
71
0
2
Order By: Relevance
“…MDA is the end product of lipid peroxidation, acts as a marker of oxidative stress [44]. It was well known that the level of MDA was elevated when the rodents exposed to DSS [6,9]. In consistent with the previous reports the level of MDA was elevated in DSS-induced mice (Fig.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…MDA is the end product of lipid peroxidation, acts as a marker of oxidative stress [44]. It was well known that the level of MDA was elevated when the rodents exposed to DSS [6,9]. In consistent with the previous reports the level of MDA was elevated in DSS-induced mice (Fig.…”
Section: Discussionsupporting
confidence: 82%
“…The mice in group 3 were orally treated with boldine at the dose of 50 mg/kg body weight for 7 days. The body weights, stool consistency, and blood in the stool were monitored every day to calculate the disease activity index (DAI) [9]. The mice were sacrificed on day 8, and the colons (from the ileocecal junction to the anal verge) were removed.…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Nrf-2, a key redox regulator, is activated by gallic acid and causes the induction of chemoresistance [131]. Similarly, a study conducted by Ashok et al 2015, also showed the ability of gallic acid to upregulate Nrf-2 activity in mice models [132]. Few recent studies have also demonstrated the ability of cinnamic acids to upregulate Nrf2.…”
Section: Adverse Effects Of Phenolic Compoundsmentioning
confidence: 99%
“…Nrf2 is a basic leucine zipper redox-sensitive transcriptional factor that serves a central role in the transcriptional regulation of antioxidant and/or detoxifying genes (19). Nuclear localization of Nrf2 activation efficiently protects cells from ROS-induced damage in vivo and in vitro by inducing the expression of numerous detoxifying enzymes and antioxidant proteins (20).…”
Section: Introductionmentioning
confidence: 99%